Model Tata Kelola Kawasan Pesisir: Strategi Pengelolaan Kawasan Pesisir Menuju Ekonomi Hijau di Kabupaten Gunung Kidul - Ardiyansah, Ardiyansah; Aziza, Pretty Failasufa; Setyawati, Kiki; Hariyadi, Ade Reza (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
This study aims to explore the management strategies of coastal areas in supporting the transition toward a green economy in Gunungkidul Regency. The management of coastal zones often faces challenges in balancing economic development with environmental sustainability. Therefore, a strategic approach that integrates social, economic, and ecological dimensions is essential. This research employs a descriptive qualitative approach, with data collected through field observations, in-depth interviews with local stakeholders, and the analysis of relevant policy documents. The findings reveal that the local government has implemented various strategies, such as enhancing active community participation in planning and monitoring, promoting participatory coastal ecosystem conservation, and integrating social values into policy formulation. These strategies are consistent with green economy principles emphasizing resource efficiency, low carbon emissions, and social equity. Moreover, efforts to strengthen local institutional capacities and foster environmentally-based microenterprises are integral components of the transition strategy. The main challenges identified include limited public literacy on sustainability, inadequate access to green technologies, and weak cross-sectoral coordination. The study concludes that strengthening multi-sector collaboration, increasing public education, and aligning policies with green development goals are essential to the successful implementation of the green economy in coastal areas. These findings are expected to provide strategic input for local governments and policymakers in designing inclusive and sustainable coastal development programs.